PERENCANAAN PRODUKSI UNTUK MEMINIMALKAN BIAYA PRODUKSI DENGAN METODA INTEGER LINEAR PROGRAMMING (Jurnal Dinamika Informatika, 2009)
Protluction plunning tcclmicul plunning 'r,t,ilh uim to give lhc optinttrm dact.srtm pursuant to resource hod the company to frlfill request a[n product. AggregatePlanning made to accomodate the ability produce in foce of dicey market request by optimum usa&e of labour and availoble production equipments so that total fareproduction can be depressed a minim possible. Aggregate word express that planning made harsh slorey;level to fuffill totalize the requirement all product to be yielded byw ing exis t ing r es ource.Keyword : Production Planning, Aggregate, Programming Linear